(untitled) (Eurasian Scientific Herald, 2024)
In the article are disclosed some conditions of integrated lessons arrangement in primary education. As well there are expressed apparent characteristics of property integrated lessons. Also, on the assumption of integrated lesson, author determined structure of given type lessons. Presented visions for that matter, reflected on example of jobs training lessons